EVALUASI PENGEMBANGAN PROFESIONALISME GURU MATA PELAJARAN EKONOMI DI SMA NEGERI KECAMATAN MUARA KUANG - Fahrianuddin Fahrianuddin; Happy Fitria; Mulyadi Mulyadi (Universitas Muhammadiyah Surakarta, 2023)
This study aimed at evaluating and describing the Professionalism Development of Economics Subject Teachers at SMA Negeri Muara Kuang District. This research is a descriptive qualitative research. This research was conducted at SMA Negeri 1 Muara Kuang and SMA Negeri 2 Muara Kuang. The research subjects were the head of SMAN 1 Muara Kuang, the head of SMAN 2 Muara Kuang, the deputy head of SMAN 1 Muara Kuang, the deputy head of SMAN 2 Muara Kuang. 2 teachers at SMAN 1 Muara Kuang, 1 teacher at SMAN 2 Muara Kuang and 2 Supervisors for Development. Data collection techniques with observation, documentation and interviews. The data analysis technique was carried out in three stages: (1) data reduction, (2) data presentation, (3) conclusion drawing. The results showed that the development of the professionalism of the Economics Subject teacher at SMA Negeri Muara Kuang District had paid attention to all aspects of the context component, implemented several aspects of the input and process components. However, the output components have not been implemented properly.